1987
DOI: 10.1590/s0074-02761987000400011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of Leishmania mexicana mexicana by Leishmania mexicana amazonensis during "in vitro" co-cultivation

Abstract: Inhibition of one Leishmania subspecies by exometabolites of another subspecies, a phenomenon not previously reported, is suggested by our recent observations in cell cloning experiments with Leishmania mexicana mexicana and Leishmania mexicana amazonensis. Clones were identified using the technique of schizodeme analysis. The phenomenon observed is clearly relevant to studies of parasite isolation, leishmanial metabolism, cross-immunity and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We have shown evidences which suggest that the presence of L. guyanensis M4147 (noninfective) presumably inhibited the development of Endotrypanum, with the drastic reduction in the number of positive females, mainly in the group of females exposed to coinfection with the heterogeneous sample (M5725) of E. schaudinni. Effects of intra-or interspecific selective pressures have already been reported previously, among co-cultivated trypanosomatids (Pacheco et al 1987, Coppens et al 1992) and even about the biology of sand flies (Alekseev et al 1975, El-Sawaf et al 1994). On the other hand, the correlation between the massive infection found in the stomodeal valve of females coinfected with L. guyanensis IM4216 and the isoenzymatic char-acterization of isolates suggest that there had been selection in the culture medium.…”
Section: Discussionmentioning
confidence: 69%
“…We have shown evidences which suggest that the presence of L. guyanensis M4147 (noninfective) presumably inhibited the development of Endotrypanum, with the drastic reduction in the number of positive females, mainly in the group of females exposed to coinfection with the heterogeneous sample (M5725) of E. schaudinni. Effects of intra-or interspecific selective pressures have already been reported previously, among co-cultivated trypanosomatids (Pacheco et al 1987, Coppens et al 1992) and even about the biology of sand flies (Alekseev et al 1975, El-Sawaf et al 1994). On the other hand, the correlation between the massive infection found in the stomodeal valve of females coinfected with L. guyanensis IM4216 and the isoenzymatic char-acterization of isolates suggest that there had been selection in the culture medium.…”
Section: Discussionmentioning
confidence: 69%
“…It has been demonstrated that in co-cultivation of more than one Leishmania the dominant species tend to inhibit the growth of the other; consequently the degree of laboratory detection of such phenomenon remains unclear and likely underestimated [28, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…The different species and subspecies of Leishmania can be distinguished by monoclonal antibodies (24), isoenzyme analysis, or restriction digests of kDNA (26,29,34,35), but these techniques require a quantity of parasites obtainable only by in vitro culture.…”
Section: Discussionmentioning
confidence: 99%